Perancangan Arsitektur Enterprise pada SMP Ibrahimy 1 Menggunakan Framework TOGAF ADM - Albi Guntara; Rifal Ardiansyah; Izzul Azmi (CV, Akira Java Bulu, 2025)
This study aims to design an Enterprise Architecture at Ibrahimy 1 Junior High School to improve the effectiveness and efficiency of school information system governance. The main problem faced is the unavailability of an integrated information system, so that the administrative process is still carried out manually. The method used is a case study approach by applying the TOGAF ADM Framework (The Open Group Architecture Framework - Architecture Development Method) which consists of nine phases of architectural development. Data were obtained through direct interviews with the school. The results of the analysis show that there is no centralized information system, the large number of students is a challenge in data management, and limited budget and human resources are the main obstacles in IT implementation. Based on these findings, an enterprise architecture blueprint was designed that can be a reference for the development of school information systems in the future. This design is expected to support the process of digitalization of education at Ibrahimy 1 Junior High School in a gradual and sustainable manner.